2011
DOI: 10.1111/j.1743-6109.2010.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dapoxetine for the Treatment of Premature Ejaculation: Integrated Analysis of Results from Five Phase 3 Trials

Abstract: Introduction Dapoxetine has been evaluated for the on-demand treatment of premature ejaculation (PE) in five phase 3 studies in various populations worldwide and has recently been approved in several countries. Aim To present integrated efficacy and safety data from phase 3 trials of dapoxetine. Methods Data were from five randomized, multicenter, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
176
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 143 publications
(190 citation statements)
references
References 49 publications
11
176
0
3
Order By: Relevance
“…An important strength of this study was the thorough and comprehensive collection of adverse event data. Compared with former studies, fewer patients were lost to follow-up (6.2% vs 3.9%, respectively) and fewer patients prematurely withdrew from the study because of the onset of a side effect induced by the drug (approximately 31% vs approximately 11%, respectively) [2].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…An important strength of this study was the thorough and comprehensive collection of adverse event data. Compared with former studies, fewer patients were lost to follow-up (6.2% vs 3.9%, respectively) and fewer patients prematurely withdrew from the study because of the onset of a side effect induced by the drug (approximately 31% vs approximately 11%, respectively) [2].…”
Section: Discussionmentioning
confidence: 84%
“…Among a total of 6081 subjects in the phase 3 studies, of whom 4224 subjects were treated with dapoxetine, the incidence of syncope was similar in patients receiving placebo and in those treated with dapoxetine 30 mg (0.05% vs 0.06%, respectively), although greater in subjects treated with the 60-mg dose (0.23%) [2]. In comparison, based on this large observational study of 6128 patients treated with dapoxetine, it was observed that the incidence of syncope was zero, with the upper bound of the 95% confidence limit around 2.0 per 1000 person-years.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations